خصوصيات الصلح القضائي كطريق بديل لتسوية المنازعات المدنية في القانون الجزائري - كيرواني ., ضاوية; زياد, محمد أنيس (unuversity of eloued- جامعة الوادي, 2022)
يعتبر الصلح أسلوبا متميزا لإنهاء المنازعات المدنية، عرفه مجتمعنا وعمل به منذ القدم. أما في العصر الحديث ونظرا لتعقد وتشعب المنازعات ما أدى إلى التراكم والتكدس القضائي، مما إنعكس سلبا على أداء جهاز القضاء. ظهرت الحاجة الملحة إلى الصلح القضائي كأحد الحلول البديلة للنزاعات. عليه، نظم التقنين المدني الجزائري الجانب الموضوعي للصلح، وأعتبره عقد ينحسم به النزاع القائم، بموجب أحكام المواد من 459 إلى 466. كما تصدى المشرع للجانب الإجرائي للصلح القضائي في قانون الإجراءات المدنية والإدارية بموجب القانون رقم 08-09، تحت عنوان: » الطرق البديلة لحل النزاعات«، من خلال تنظيم إجراءاته بموجب المواد 990 إلى 993. Conciliation is considered as a distinct method to end civil conflict, which is known and practiced by our society and people since ancient times. However in the modern age, the complexity of nowadays conflicts has led to backlogs and accumulation in judicial proceedings that had a negative impact on the judiciary performance. Thereupon, the urgent need for judicial conciliation seems to be an appropriate alternative in disputes settlement. Accordingly, the Algerian civil legalization regulated substantial measures for conciliation and considered it as an agreement that solves both existing and potential dispute, under the provisions of Article 459 to Article 466. The Algerian legislator tackled the procedural aspect of judicial conciliation in the Code of Civil and Administrative Procedure under No 08-09, entitled ‘Alternative methods for disputes settlement’ by regulating its procedures under Articles 990 to 993.
Judicial conciliation specificities as an alternative to settle civil conflicts in Algerian law
مقال
Keywords: الصلح القضائي ; جوازي، محضر ; سند تنفيذي; Judicial conciliation, permissible, minutes, enforceable instrument.